ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI PEMBIAYAAN BAGI HASIL PADA BANK PEMBIAYAAN RAKYAT SYARIAH - Asyifa Zahrah Fitria (2022)
This research is a quantitative research that has the aim of analyzing the effect of return on assets (ROA), capital adequacy ratio (CAR), financing to deposit ratio (FDR), non performing financing (NPF) and operational efficiency ratio (OER) on profit sharing financing proxied by profit sharing ratio (PSR). The data used in this research is secondary data in the form of annual financing reports from Sharia Rural Banks registered with the Financial Services Authority during the 2018-2020 period. The sample selection was carried out by purposive sampling technique with a total of 158 SRB as a sample. Hypothesis testing is done by using panel data regression analysis. The processed regression model has been tested using the STATA application. This research obtained results are (1) ROA has a positive effect on profit sharing financing, where the higher ROA can affects the increase in profit sharing financing distributed, (2) CAR has no effect on profit sharing financing, meaning that the high/low value of CAR has no effect on the profit sharing financing, (3) FDR has no effect on profit sharing financing, meaning that the high/low value of FDR has no effect on the profit sharing financing, (4) NPF has a positive effect on profit sharing financing, meaning that the higher NPF can affects the increase in profit sharing financing dan (5) OER has a positive effect on profit sharing financing, which means the higher OER can affects the increase in profit sharing financing